Investigation of the Efficiency of Photovoltaic Thermal (PV/T) Hybrid Collector as Solution for Water Desalination Needs of Rural Areas in Niger - Mariama Alı Garba; Bulent YESILATA (Journal of Innovative Science and Engineering)
The efficiency of SS (single slope) solar still integrated with a Photovoltaic-thermal collector (PVT) is investigated underneath Niamey’s climatic weather conditions. Thus, a theoretical study is conducted, and MATLAB software is used to simulate the equations and data of climatic conditions in Niamey. Three different months have been used for the computations. The electrical efficiency and thermal power of the PVT structure, along with the temperatures of water and glass cover are determined. Also, the daily freshwater yield and overall thermal efficiency of the system are calculated. As a result, the maximum electrical and thermal efficiencies of this structure at noon are found to be 14% and 58.09% respectively. The maximum temperature of water is recorded to be 60 ℃ while that of the glass cover is reported to be 51.4 ℃. The highest freshwater production rate is observed to be 1.10 kg/m2 per hour at noon time, and the daily freshwater yield is 2.62 kg/m2 .